Brain circulation and the role of the diaspora in the Balkans - Albania, Kosovo, Macedonia - Hristina Cipusheva; Sokol Havolli; Fatmir Memaj; AbdulGhaffar Mughal; Bardha Qirezi; Artane Rizvanolli; Luljeta Sadiku; Abdulmenaf Sejdini; Esmeralda Shehaj (South East European University, 2013)
Countries of the Western Balkans constitute an important part of the contemporary system of migration. Three important factors shape the current migration flows in the region: the socialist legacy, existing migrant networks, and migration policies, mainly of the receiving countries. This study focuses on three countries of the Western Balkans: Albania, Macedonia, and Kosovo. Unlike nationals of Albania, whence exit was near impossible, citizens of Macedonia2 and Kosovo, being constituent parts of the former Yugoslavia, enjoyed relative freedom of movement across Europe and they have traditionally been source countries of labor migration. The collapse of the socio-economic and political order that attended upon the breakup of the former Yugoslavia was accompanied by ethnic conflicts of the 1990s, high unemployment, and general impoverishment of large sections of the population. These factors, coupled with the onset of transition to a market economy, further strengthened the networks of labor migration throughout Europe that were created by nationals of the Western Balkan. The refugee regimes and immigration policies of major destination countries of the OECD played a significant role in this process. Today, many of these countries contain the bulk of the diaspora from the Western Balkans, including the three countries under study
Keywords: J61; J62; 330; Brain circulation; Migration; Macedonia; Albania; Kosovo; Brain circulation; Migration; Macedonia; Albania; Kosovo